Évaluation et risques sanitaires de la bioaccumulation de métaux lourds chez des espèces halieutiques du système lagunaire togolais - Kamilou Ouro-Sama; Hodabalo Dheoulaba Solitoke; Kissao Gnandi; Komlan Mawuli Afiademanyo; Essô Joseph Bowessidjaou (VertigO)
Bioaccumulation of cadmium, lead and arsenic in fish and bivalves commonly caught in Togo lagoon system was evaluated in order to estimate the health risks associated with their use. The results showed that all analyzed fish are contaminated. The mean levels of cadmium (0.33 mg/kg for Caranx hippos to 0.98 mg/kg for Hemichromis fasciatus), lead (1.17 mg/kg for Liza falcipinnis to 2.89 mg/kg for Lutjanus goreensis ) and arsenic (9.41 mg/kg for C. hippos to 22.54 mg/kg for Pomadasys jubelini) are higher than the standards set by the WHO. Bioconcentration Factors (BCF) ranged from 6.94 to 20, 36 for Cd, 9.58 to 23.67 for Pb and 2.30 to 5.52 for As. As far as bivalves are concern, average grades indicate a high concentration of arsenic (56.06 mg/kg for Senilia senilis and 47.76 mg/kg for Crassostrea gasar) followed by lead (2.83 mg/kg for S. senilis and 2.95 mg/kg for C.gasar) and finally cadmium (0.97 mg/kg for S. senilis and 0.83 mg/kg for C.gasar). BCF ranged from 16.6 to 19.14 for Cd, 39.86 to 41.55 for Pb and 19.10 to 34.42 for As. In addition,